Pengaruh Budaya Organisasi, Motivasi Kerja Dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Karyawan (Studi Pada PT. Harmoni Panca Utama Site MGA Murung Raya Kalimantan Tengah) - Hasbuloh, Ach Zufri; Taharudin, Taharudin (Universitas Lambung Mangkurat, 2023)
This study aims to examine and determine the effect of organizational culture, work motivation and transformational leadership style on employee performance through employee job satisfaction. This study used a quantitative approach with the number of samples used for this study were 279 samples who were employees at PT. Harmoni Panca Utama site MGA in Murung Raya, Central Kalimantan. The research data was processed using the SmartPLS 3.2.9 analysis tool and the research method in this study used Structural Equation Modeling (SEM). The results of this study indicate that organizational culture, work motivation and transformational leadership style have a positive and significant effect on employee performance at PT. Harmoni Panca Utama site MGA. The results also show that employee job satisfaction has an indirect effect in mediating the impact on the relationship between organizational culture, work motivation and transformational leadership style on employee performance at PT. Harmoni Panca Utama site MGA. Keywords: Organizational Culture, Work Motivation, Transformational Leadership, Employee Performance, Job Satisfaction